Wellness Tourism in Puncak West Java Indonesia Area - Pujiastuti, Sri (E-Journal of Tourism; Volume 6 Number 2 (September 2019)DO - 10.24922/eot.v6i2.53473, 2019)
Wellness tourism is one of the attractions that has become a trend both in Indonesia and in the world, in addition to providing business opportunities and can also have a positive impact on health and fitness that have not been managed optimally. The area that has the potential of wellness tourism is in Puncak area which is found in West Java, especially in the PTP Nusantara VIII Gunung Mas area, which has a tea plantation as well as a spring in it. The distance that is not too far from the capital city of Jakarta, makes this area a tourist destination for escape or relaxation from routine activity. This study uses a descriptive qualitative approach where data collection uses in-depth interviews, documentation and review literature from various sources and where the results obtained are presented thoroughly to get a complete picture of the potential of wellness tourism in the peak regions. The results obtained in this study are that the management and regulation of wellness tourism are felt appropriate to be developed in this area, due to the natural potential possessed in accordance with the background or motivation of tourists who come to this area. In addition, wellness tourism that is based on nature and managed jointly with the local community will contribute positively to the improvement of the economy of the surrounding community and environmental preservation that will be maintained over time. Keywords: Wellness Tourism, Puncak area